1997
DOI: 10.1002/(sici)1097-4660(199709)70:1<99::aid-jctb684>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ammonium and methods for removal during the anaerobic treatment of poultry manure

Abstract: : The addition of exogenous to poultry manure and synthetic NH 4Cl medium was used to study the e †ect of ammonia-nitrogen on the activity and composition of a methanogenic consortium. Results indicated that the production of biogas and methane was not a †ected by the variation in con-NH 4 Cl centration within the range 2È10 g dm~3 (0É5È2É6 g dm~3). At higher N-NH 4 values of ammonium (10È30 g dm~3 or 2È8 g dm~3) a signiÐcant N-NH 4 decline in both parameters (by 50È60% for biogas and 80È90% for methane) was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(35 citation statements)
references
References 3 publications
0
31
1
3
Order By: Relevance
“…Following anaerobic digestion of poultry feces for 37 days, both coliform and E. coli counts decreased drastically. It was also reported by Krylova et al [129] that high levels of ammonium (>30 g/L) during anaerobic digestion of poultry litter resulted in a decrease in the numbers of all physiological microbial groups. A study on bacteriophage has also demonstrated its effectiveness for biological control of pathogens in compost.…”
Section: Biological Control Techniquesmentioning
confidence: 58%
“…Following anaerobic digestion of poultry feces for 37 days, both coliform and E. coli counts decreased drastically. It was also reported by Krylova et al [129] that high levels of ammonium (>30 g/L) during anaerobic digestion of poultry litter resulted in a decrease in the numbers of all physiological microbial groups. A study on bacteriophage has also demonstrated its effectiveness for biological control of pathogens in compost.…”
Section: Biological Control Techniquesmentioning
confidence: 58%
“…AD is the most efficient practice for the management of PM because of the renewable biogas energy it provides and because of the suitability of the digested matter as a fertilizer for planting (Walsh et al 2012;Xie et al 2012;Giuliano et al 2013;Muller et al 2013). However, the C/N ratio of PM is within the range of 9.8 to 14.5 (Zhang et al 2014a), which often leads to ammonia inhibition (Krylova et al 1997;Hansen et al 1998;Procházka et al 2012;Wang et al 2012b;Niu et al 2014) because free ammonia molecules passively diffuse into cells, which causes a proton imbalance and/or a potassium deficiency that inhibits the growth of methanogens (Chen et al 2008). To dilute toxic compounds, it is essential to maintain a proper C/N ratio (20 to 30).…”
Section: Introductionmentioning
confidence: 99%
“…This TS concentration inside the reactor is appropriate for the anaerobic digestion of solid wastes, because the reported suitable range is between 10 and 50 g/L of TS [11][12][13]. The reported inhibitory ammonium concentration for methanogenic bacteria is between 3.5 and 18.3 g/L [12,[14][15][16][17][18][19][20][21]. With an increase on the organic loading rate (from 1.5 to 2.5 kgVS/m 3 d) the total solids and ammonium concentrations increased gradually, over 50.0 and 5.0 g/L respectively, exceeding the recommended concentrations for biomethanization which could negatively affect the reactor behaviour.…”
Section: Analytical Methodologymentioning
confidence: 96%